Níveis e fontes de manganês sobre o desempenho e a resistência óssea em frangos de corte - Guilherme Santos Bassi (2020)
The objective of this study was to determine the ideal level of manganese supplementation (Mn) for broilers, evaluating in two experiments two sources, chelated (linked to amino acid) and inorganic (oxide) that guarantees the necessary bone quality, to support the growth process, catching, transport and slaughter. The experimental period was from the birds’ first to 35th day of life, in which an amount of 1260 male Cobb® strain broilers of the were used, distributed in a completely randomized design in four treatments of six replications with 30 birds each. The treatments were defined by supplementing a diet based on a corn and soybean meal, with supplementary levels of 0, 35, 70 and 105 mg of manganese / kg of feed in the form of manganese oxide (Chapter II) or amino acid manganese (Chapter III). In both experiments, feed intake, weight gain, feed conversion, viability and productive efficiency index were evaluated as performance parameters. For bone quality, the Seedor index, bone ash, concentrations of manganese, calcium and phosphorus in the femur and bone strength were evaluated. The occurrence of injuries or bone fractures was observed in the slaughter line of a commercial slaughterhouse from the moment of hanging up to the cut of the feet and no incidence of bruises or traumatic bone injuries was observed. Among the levels of manganese supplementation in inorganic form (MnO), there were no differences in performance variables, Seedor index, phosphorus concentration, ash and bone strength of broilers. In the femur, concentrations of manganese and calcium showed a significant difference (P <0.05), with an estimated manganese requirement for broilers of 57.36 mg of higher manganese/kg for manganese concentration and 81.07 mg manganese/kg for higher calcium concentration. For the levels of supplementation of manganese in its chelated form (Mn amino acid), there were no differences in the performance variables: Seedor index, concentrations of manganese and phosphorus, ash and bone strength of broilers. The calcium concentration in the femur showed a significant difference (P <0.05), with an estimated manganese requirement for broilers of 73.13 mg of manganese / kg for a higher concentration of calcium in the femur. In fact, manganese supplementation in a diet based on corn and soybean meal is not necessary for broilers to have good performance and bone quality.